Cooperviva: análise das possibilidades e limites do trabalho dos catadores de resíduos recicláveis de Rio Claro (SP) - Franceschini, Guilherme [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
The issue of waste, historically, has been getting worse as a result of the world´s population increase and in order to meet their needs the consumption of natural resources and the generation has been constantly increasing, especially in large urban centers. The people involved in the collection of recyclable solid waste, called from now on as collectors, are responsible for about 90% of the waste sent to recycling industry in Brazil. Apart from having a role in the economy, the collectors have specific knowledge and skills necessary to identify, collect, sort and sell these wastes. This study aims to examine the possibilities and limits of COOPERVIVA – Cooperativa de Trabalho dos Catadores de Material Reaproveitável de Rio Claro - as an instrument of the municipal solid waste management system, and its experience as a recyclable waste collectors cooperative. The methodological procedures of this study rely on the literature research on the experiences of cooperative and the management of municipal solid waste. In addition to this review of the literature, fortnightly visits to the cooperative were held in order to experience their daily activities, and testimonies of the cooperative members were collected as well as documents and reports produced by COOPERVIVA. The results of this analysis are considerations of the limitations of the cooperative and recommendations aimed at maximizing their potential as a tool of the domestic solid waste management system of and as a recyclable waste collectors cooperative. Among other things it can be concluded that the urban selective collection of waste challenges the community to the reinvention of life and the relationships each individual with the planet.

A problemática dos resíduos, historicamente, vem se agravando na medida em que a população mundial aumenta, pois para atender as suas necessidades, o consumo dos recursos naturais e a geração de resíduos se tornam cada vez maior, principalmente, nos grandes centros urbanos. Os catadores de resíduos sólidos são responsáveis por cerca de 90% dos resíduos que alimentam as indústrias de reciclagem no Brasil. Além de terem um papel na economia, possuem os conhecimentos específicos e as habilidades necessárias para identificar, coletar, separar e vender estes resíduos. Este estudo pretende analisar as possibilidades e limites da COOPERVIVA - Cooperativa de Trabalho dos Catadores de Material Reaproveitável de Rio Claro como instrumento do sistema de gestão de resíduos sólidos domiciliares, bem como a sua experiência como uma cooperativa de catadores de resíduos recicláveis. Os procedimentos metodológicos deste estudo contam com a pesquisa bibliográfica sobre as experiências do cooperativismo e da gestão dos resíduos sólidos domiciliares. Além desta revisão da bibliografia, foram realizadas visitas quinzenais à cooperativa, para acompanhar suas atividades cotidianas, e foram recolhidos depoimentos e relatos de seus cooperados assim como os documentos e relatórios produzidos pela COOPERVIVA. Os resultados obtidos com esta análise são apontamentos das limitações da cooperativa e recomendações que visem maximizar as suas possibilidades como instrumento do sistema de gestão de resíduos sólidos domiciliares e como uma cooperativa de catadores de resíduos recicláveis. Entre outras coisas pode-se concluir que a coleta seletiva do lixo no meio urbano desafia a comunidade para a reinvenção da vida e das relações de cada indivíduo com o planeta.
Keywords: Resíduos; Resíduos sólidos domiciliares; Cooperativas de catadores; Coleta seletiva; Cadeia produtiva da reciclagem; Municipal solid waste; Collectors cooperatives; Selective collection